LEGAL INSTRUMENTS FOR PERSONAL DATA PROTECTION IN BIG DATA ANALYSIS: CONSENT AND CONTRACTS (TSUL LEGAL REPORT, 2026)
This article examines the legal aspects of personal data processing conditions and contractual relations in the context of Big Data. The importance of consent in the placement and use of personal data on digital platforms and social networks, user agreements, and mechanisms for obtaining consent for personal data processing have been studied in detail. A comparative analysis of consent requirements established in international documents such as the GDPR, CCPA, PIPA, and the legislation of Uzbekistan has been conducted. Issues related to processing personal data based on legitimate interests in Big Data analysis, and balancing these interests with individual rights and freedoms have been investigated. Problems associated with data processing based on contractual obligations, the activities of data brokers, and the use of publicly posted data on social networks have also been studied. New innovative methods of data processing, particularly step-by-step consent, context-based consent, and automated consent systems, have been analyzed. The legal nature of user agreements on digital platforms as mixed contracts containing elements of license agreements and service agreements has been substantiated. Modern mechanisms for protecting data subjects’ rights, including procedures for obtaining data subjects’ consent in automated decision-making and profiling, have been proposed. Based on the research results, practical recommendations for improving national legislation have been developed, particularly proposing additions and amendments to the Law “On Personal Data.”